2017
DOI: 10.1016/j.psychres.2016.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in schizophrenia: A meta-analysis of the Interpersonal Reactivity Index

Abstract: Empathy is a complex construct, thought to contain multiple components. One popular fourfactor conceptualization has been used extensively to measure empathy in schizophrenia research (empathic concern, perspective-taking, personal distress, and fantasy); however, no recent metaanalysis has been conducted on the four factors together. The goal of this meta-analysis was to examine self-reported empathy for each component in the four-factor conceptualization in people with schizophrenia as compared to healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 77 publications
9
62
2
1
Order By: Relevance
“…But other three-dimensions (Empathic concern, Perceptive-taking and Fantasy) shows notably lower which is consistent with the literature by Fengfeng Zhang [27]. Also, the results of self-reports are opposed to behavioral tests [31]. The discrepancy in personal distress might be cultural difference.…”
Section: Disscusionsupporting
confidence: 88%
See 2 more Smart Citations
“…But other three-dimensions (Empathic concern, Perceptive-taking and Fantasy) shows notably lower which is consistent with the literature by Fengfeng Zhang [27]. Also, the results of self-reports are opposed to behavioral tests [31]. The discrepancy in personal distress might be cultural difference.…”
Section: Disscusionsupporting
confidence: 88%
“…A meta-analysis [31] reported schizophrenics suffered from all-round empathy impairment. They cannot stand on the others' point to consider problems, especially in daily interaction.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In schizophrenia, deficits in social cognition and metacognition lead to poor social functioning and isolation [9]. Plenty of studies so far demonstrated a clear empathic deficit in all empathic domains in schizophrenia [10][11][12][13][14][15][16]. In these studies, empathic deficits were assessed with different methods, ranging from computer tasks to self-report questionnaires, all detecting significant empathic impairments in patients.…”
Section: Introductionmentioning
confidence: 99%
“…2009). Ayrıca pot kırmayı anlama ve empati becerisinde bozulma olduğu yönünde de bulgular vardır (Bonfils ve ark. 2016, Ozel-Kizil ve ark.…”
Section: Introductionunclassified